Systematic Review and Bibliometric Analysis of Sustainable Agricultural Partnership Models - Perdana, Indra; Khatami, Muhammad Mahesa; Pranoto, Moch Fadli Wijaya; Zuhri, Nur Muttaqien (Economics and Business International Conference Proceeding, 2024)
Agricultural partnerships establish important sustainability principles that can deepen environmental and social responsibility in agricultural systems and improve the performance of compliant organizations. However, the performance of partnerships in developing countries cannot compete in international markets due to non-compliance with sustainability schemes in economic, social and environmental aspects. Meanwhile, there is little coherent review of the knowledge landscape related to partnership models and business perceptions in driving partnership performance. Therefore, this study conducted a comprehensive systematic review and bibliometric analysis of the existing literature to provide insights into publication trends, critical articles and contributing research sponsors. It was revealed that, partnership models and partner performance are underrepresented, with Indonesia being the most influential contributor in studies related to agricultural partnership compliance. Although the influence of most factors in the existing literature is mixed, this study recommends increased international research partnerships to foster the development of the knowledge field of partnership digitalization, which appears to be experiencing maturation challenges, plus progressive research on sustainable models in underrepresented contexts. Policy responses to improve the organizational performance of businesses through digitization and rule regulation are also suggested.